Who is the Building Leader?: Commentary on Educational Leadership Preparation Programs for the Future - Debbie K. Mercer (Educational Considerations, 2016)
It is critical that educator preparation programs reflect the current and future needs of schools. The job of a school leader is more complex and more demanding than ever before.
Keywords: Kansas State University; schools; principals and teacher; school districts; Educational Leaders; Job Description; positions; Kansas